Proton pump inhibitor treatment is associated with the severity of liver disease and increased mortality in patients with cirrhosis. Issue 5 (19th December 2014) - Dultz, G.; Piiper, A.; Zeuzem, S.; Kronenberger, B.; Waidmann, O.
Summary Background Proton pump inhibitors (PPI) are widely used in patients with liver diseases. Within the last years, there have been concerns about the PPI use as they may promote infections in patients with cirrhosis. Aim As there are sparse data of the prognostic relevance of PPI treatment, to perform a prospective study investigating the relation of PPI treatment and overall survival (OS) in cirrhotic individuals. Methods Patients with cirrhosis were enrolled and followed prospectively. The primary end point was OS. PPI treatment and additional clinical and laboratory data were assessed at the day of the study inclusion. The time until the end point death was assessed and the individual risks were calculated with Cox regression analyses. Results A total of 272 patients were included and 213 individuals (78.3%) were on PPI treatment. In multivariate logistic regression analysis, PPI treatment was associated with higher MELD scores (P = 0.027) and ascites (P = 0.039). In a multivariate Cox regression model, PPI use was an independent predictor of mortality (hazard ratio 2.330, 95% confidence interval 1.264–4.296, P = 0.007) in addition to the model of end‐stage liver disease (MELD) score, hepatocellular carcinoma and hepatic decompensation. Conclusions PPI use is an independent risk factor for mortality in patients with cirrhosis. Although a causative role for increased mortality in patients taking PPI is still missing, the prescription of PPI in cirrhotics should be considered carefully taking into account its potential adverse effects.